TRANSFORMATION OF RISKS AND THREATS OF THE ECONOMIC SECURITY OF DOMESTIC BUSINESS ENTITIES (Development Service Industry Management, 2023)
The article analyzes the main risks and threats to the economic security of domestic enterprises-subjects of foreign economic activity. The state of functioning of enterprises of key branches of industry in the conditions of martial law, in particular enterprises of the metallurgical and agricultural industries, was studied. It is determined that the metallurgical industry has experienced a more than 70% reduction in production as of the end of 2022. The work analyzes the dynamics of export-import operations over the past two years. It became clear that over the last year there was a drop in the volume of export of domestic products and import. Changes also took place in traditional foreign trade relations in favor of the countries of the European Union. The article analyzes changes in the geographic structure of foreign trade over the past year. The main risks and threats faced by domestic enterprises are identified. These include: the loss of production potential, in particular due to hostilities in the territory where production facilities are located, the reduction in the volume of industrial production, the loss of logistical routes for the implementation of export-import operations due to the blocking of sea ports and the low capacity of railways and roads, a change in the vector of foreign trade. Most of the losses in the agro-industrial sector were caused by damage and even destruction of agricultural lands, as well as by the impossibility of harvesting crops in the territory of hostilities or the territory close to it. In addition, it was determined that a significant threat to the functioning of domestic industrial enterprises today is the shortage of electricity, which affects the general activity of each enterprise.
Keywords: economic security; industrial enterprises; foreign economic activity; risks; threats; foreign trade